Membangun Masyarakat Mandiri melalui Pengembangan Usaha Gerabah di Desa Sukarara Lombok Timur - Drajad, Danang (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to analyze the development potential of the pottery business in fostering a self-reliant community in Sukarara Village, East Lombok. Sukarara Village is renowned for its traditional pottery craftsmanship, which serves as a symbol of local cultural identity. Despite its great potential, the local community still faces several challenges, including product marketing, business management, and human resource capacity development. Through an empowerment approach, this research proposes a development strategy for the pottery business, which includes production skill training, product innovation to expand market reach, and improved access to local and national markets. Furthermore, this study emphasizes the importance of collaboration between the government, educational institutions, and the community in creating a supportive ecosystem for pottery business development. Thus, the pottery business is expected not only to enhance the economic well-being of the community but also to build their independence in managing and developing their businesses sustainably. This study is expected to contribute to a model of community empowerment based on local potential, which can be implemented in other regions with similar characteristics.